2022
DOI: 10.1002/cbf.3709
|View full text |Cite
|
Sign up to set email alerts
|

Computational targeting of allosteric site of MEK1 by quinoline‐based molecules

Abstract: MEK1 is an attractive target due to its role in selective extracellular‐signal‐regulated kinase phosphorylation, which plays a pivotal role in regulating cell proliferation. Another benefit of targeting the MEK protein is its unique hydrophobic pocket that can accommodate highly selective allosteric inhibitors. To date, various MEK1 inhibitors have reached clinical trials against several cancers, but they were discarded due to their severe toxicity and low efficacy. Thus, the development of allosteric inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Computer-aided drug design (CADD) involves high-throughput screening of selective ligands to agonize or antagonize target structures [7,8]. CADD relies on the assumption that candidate compounds have affinity to protein targets with minimum side effects while having sufficient absorption, distribution, metabolism and excretion (ADME) properties [9,10]. Some promising malaria compounds that have recently progressed to clinical evaluation include KAE609 [11], M5717 [12], MMV390048 [13] and others [14].…”
Section: Introductionmentioning
confidence: 99%
“…Computer-aided drug design (CADD) involves high-throughput screening of selective ligands to agonize or antagonize target structures [7,8]. CADD relies on the assumption that candidate compounds have affinity to protein targets with minimum side effects while having sufficient absorption, distribution, metabolism and excretion (ADME) properties [9,10]. Some promising malaria compounds that have recently progressed to clinical evaluation include KAE609 [11], M5717 [12], MMV390048 [13] and others [14].…”
Section: Introductionmentioning
confidence: 99%
“…12 Several research studies have utilized contemporary computational techniques to identify the small molecule inhibitors and structural mechanisms that help experimental researchers to test the drugs in vivo and in vitro, for targeted therapy. [13][14][15] We integrated pharmacophore modeling with many such approaches for mutationspecific K-Ras drug development to determine the compounds targeting K-Ras G13D. This was done by generating pharmacophore hypotheses utilizing the recognized inhibitory compounds to generate a model with all the characteristics needed for the prospective drug.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified several FDA‐approved inhibitors targeting G12C and G12D K‐Ras models using pharmacophore modeling and a drug‐repurpose approach 12 . Several research studies have utilized contemporary computational techniques to identify the small molecule inhibitors and structural mechanisms that help experimental researchers to test the drugs in vivo and in vitro, for targeted therapy 13–15 . We integrated pharmacophore modeling with many such approaches for mutation‐specific K‐Ras drug development to determine the compounds targeting K‐Ras G13D.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, these restrictions have supported researchers to have better insight to understand the molecular processes that underlie the onset of different stages of cancer (Jayashree et al 2015 ). In the light of this, much efforts are being made so as to identify and validate newer targets in cancer biology (Singh et al 2022 ). Some of the anticancer targets that are presently identified in the clinical set up includes tyrosine kinase (Bhardwaj et al 2020 ), Farnesyl transferases, histone deacetylases, aromatase and cyclin-dependent kinases (CDKs).…”
Section: Introductionmentioning
confidence: 99%